Effect of hands-on interprofessional simulation training for local emergencies in Scotland: the THISTLE stepped-wedge design randomised controlled trial. Issue 2 (13th July 2019) - Lenguerrand, Erik; Winter, Cathy; Siassakos, Dimitrios; MacLennan, Graeme; Innes, Karen; Lynch, Pauline; Cameron, Alan; Crofts, Joanna; McDonald, Alison; McCormack, Kirsty; Forrest, Mark; Norrie, John; et al.
Abstract : Objective: To assess whether the implementation of an intrapartum training package (PROMPT (PRactical Obstetric Multi-Professional Training)) across a health service reduced the proportion of term babies born with Apgar score <7 at 5 min (<7 5mins ). Design: Stepped-wedge cluster randomised controlled trial. Setting: Twelve randomised maternity units with ≥900 births/year in Scotland. Three additional units were included in a supplementary analysis to assess the effect across Scotland. The intervention commenced in March 2014 with follow-up until September 2016. Intervention: The PROMPT training package (Second edition), with subsequent unit-level implementation of PROMPT courses for all maternity staff. Main outcome measures: The primary outcome was the proportion of term babies with Apgar<7 5mins . Results: 87 204 eligible births (99.2% with an Apgar score), of which 1291 infants had an Apgar<7 5mins were delivered in the 12 randomised maternity units. Two units did not implement the intervention. The overall Apgar<7 5mins rate observed in the 12 randomised units was 1.49%, increasing from 1.32% preintervention to 1.59% postintervention. Once adjusted for a secular time trend, the 'intention-to-treat' analysis indicated a moderate but non-significant reduction in the rate of term babies with an Apgar scores <7 5mins following PROMPT training (OR=0.79 95%CI(0.63 to 1.01)). However, some units implemented the intervention earlier than their allocated step, whereas others delayed the intervention. The content and authenticity of the implemented intervention varied widely at unit level. When the actual date of implementation of the intervention in each unit was considered in the analysis, there was no evidence of improvement (OR=1.01 (0.84 to 1.22)). No intervention effect was detected by broadening the analysis to include all 15 large Scottish maternity units. Units with a history of higher rates of Apgar<7 5mins maintained higher Apgar rates during the study (OR=2.09 (1.28 to 3.41)) compared with units with pre-study rates aligned to the national rate. Conclusions: PROMPT training, as implemented, had no effect on the rate of Apgar <7 5mins in Scotland during the study period. Local implementation at scale was found to be more difficult than anticipated. Further research is required to understand why the positive effects observed in other single-unit studies have not been replicated in Scottish maternity units, and how units can be best supported to locally implement the intervention authentically and effectively. Trial registration number: ISRCTN11640515 .